Oral creatine supplementation improves multiple sprint performance in elite ice-hockey players - Jones, A. M.; Atter, T.; George, K. P. (Medicine & Science in Sports & Exercise, 1998)
Elite ice-hockey players (N = 16) were assigned to either a placebo or creatine supplementation group. After an initial week of 4 x 5 gm/d supplementation, a maintenance regimen (5 gm/d) was instituted for 10 weeks. Performance was assessed by a Wingate cycle test and six timed 90-m skating sprints (one every 30 seconds). Testing was performed before the supplementation, after 10 days, and after 10 weeks. The placebo group did not change in any variables over the time of the investigation. The creatine supplementation group improved in sprint performance, mean power output, and peak power after 10 days. Improvements were maintained in the supplementation group in mean power output and on-ice sprint performance at 10 weeks. Implication. Creatine supplementation had an ergogenic effect on sprinting performance in elite ice-hockey players.